Cost of Serum Versus Skin Allergy Testing Among Medicare Fee-for-Service Beneficiaries in the United States - Kenny Y. Kwong; Yang Z. Lu (Journal of Health Economics and Outcomes Research)
**Background:** Testing for allergic sensitization can be achieved similarly via skin or serum specific immunoglobulin E (sIgE) testing, although the costs of each method differ.